Total hip arthroplasty in Brazil, 2012-2021 (Research, Society and Development, 2023)
Objectives: to evaluate the benefit of total hip arthroplasty in functional recovery, early rehabilitation and reduction of sequelae in the treatment of pathologies of the proximal femur. Materials and methods: a retrospective epidemiological, qualitative and quantitative study, whose data were obtained by consulting the Ministry of Health - Health Information (TABNET) databases, made available by the Departamento de Informática do Sistema Único de Saúde (DATASUS). The study population is made up of patients submitted, in Brazil, to the hip arthroplasty procedure during the period 2012 - 2021. We evaluated the number of hospital procedures, the sites with the highest numbers of care provided, the value of hospital and professional services, the length of hospital stay and the number of deaths related to the procedure. Results: 251,413 hip arthroplasty procedures were recorded, and cementless total hip arthroplasty was the most commonly used technique (33.1%), followed by partial hip arthroplasty (29.2%), accounting for an average of 7.8 days of hospitalization. Conclusion: Hip arthroplasty is a procedure that is being increasingly used in the treatment of coxarthrosis and proximal femur fracture, and it is an effective treatment when well indicated.